(untitled) (Agroindustria, Sociedad y Ambiente, 2013)
The plant pigweed ( Amaranthus dubius Mart) has high nutritional value and high protein vegetable motivated to incorporate it as an ingredient in the form of flour in making cookies in order to evaluate its effect on the physicochemical characteristics with different percentages (4 , 8, 12 , 16 and 20 % ) . For data analysis one way ANOVA was used, the samples that reflected differences between them were analyzed by the Tukey test, with a probability (P < 0.05 ) using the statistical package Stagraphics Centurion . In conclusion it was determined that the cookies increased significantly its physicochemical characteristics, values between protein content ( 11.44 to 14.66 ) fiber ( 0.43 to 6.68 % ) and fat ( 16 were achieved , 81 to 20.39 % ) , fly ash ( 1.27 to 6.82 ), whereas the percentages of carbohydrates decreased ( 70.03 to 56.3 ) ) and humidity ( 3.85 to 2.95 ) as including the percentage of amaranth flour increased , constituting an alternative as an ingredient in the development of functional foods rich in protein and fiber.